1997
DOI: 10.1021/ie970185r
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Resin-Type Adsorbents for Ethane/Ethylene Separation

Abstract: Modified adsorbents, Ag+-exchanged resins, have been prepared and studied for ethane/ethylene separation by adsorption. On Ag+-exchanged Amberlyst 35 (36.5% exchange) at 25 °C and 1 atm, the equilibrium adsorbed amount for C2H4 is 1.48 mmol/g, and the equilibrium adsorption ratio for C2H4/C2H6 is 6.4. The adsorption capacity is completely restored at 100−105 °C, although small residual amounts exist after desorption at 25 °C and 75 °C. For the adsorption encompassing both physical adsorption and π-complexation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 14 publications
1
51
0
Order By: Relevance
“…Moreover, FTIR spectral analysis of the regenerated MSTLP revealed that it had the same chemical nature as did MSTLP. Table 3 presents the comparative ethylene adsorption capacities of MSTLP and of some other economical adsorbents as obtained from a literature review (Wu et al, 1997;Wills and Warton, 2004;Kima et al, 2005;Liu et al, 2006;Albunia et al, 2008). Generally, zeolites and carbon-based materials are used as absorbents for the removal of ethylene.…”
Section: Regeneration Studiesmentioning
confidence: 99%
“…Moreover, FTIR spectral analysis of the regenerated MSTLP revealed that it had the same chemical nature as did MSTLP. Table 3 presents the comparative ethylene adsorption capacities of MSTLP and of some other economical adsorbents as obtained from a literature review (Wu et al, 1997;Wills and Warton, 2004;Kima et al, 2005;Liu et al, 2006;Albunia et al, 2008). Generally, zeolites and carbon-based materials are used as absorbents for the removal of ethylene.…”
Section: Regeneration Studiesmentioning
confidence: 99%
“…The similar adsorption uptakes at equilibrium could be due to a compensatory energetic effect, as a result of the specific interactions of the quadrupole moment (δ) and the polarizability (α) of the (Table 4): δ(CO 2 ) > δ(C 2 H 4 ) and α(C 2 H 4 ) > α(CO 2 ). Hence, the adsorption separation of this gaseous mixture using Cp may be achieved by virtue of the differences in the diffusion rates of these molecules (Yang 1997) observed at short adsorbent-adsorbate contact time, t < 10 s. However, Cp-H cannot be recommended for the separation of CO 2 /C 2 H 4 mixtures since its capacity for adsorbing CO 2 and C 2 H 4 is respectively lower and higher than that of the other samples studied (see Figure 9). The low irreversible adsorption of C 2 H 4 ( Figure 5) and the considerable reversible adsorption of CO 2 onto Cp-Na detected at 0 ºC enable this sample to be recommended as a suitable adsorbent for the good separation of a CO 2 /C 2 H 4 mixture at 0 ºC.…”
Section: Co 2 /C 2 Hmentioning
confidence: 99%
“…The search for a suitable adsorbent has been relentless; thus, Ackley and Yang (1991a,b) have modified natural zeolites chemically to improve their adsorption properties. It has been reported by Wu et al (1997) that the application of resin-type materials modified by Ag + ion-exchange leads to the complete restoration of the adsorption capacity towards ethylene at 100-105 ºC. Padin and Yang (2000) reported that new adsorbents for ethane/ethylene and propane/propylene separations could be prepared by dispersing AgNO 3 over γ-Al 2 O 3 , SiO 2 and MCM-41 substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Various metals ions especially Ag [7][8][9], Cu [10,11] and Pd [12], alone are mixed [13] and supported on porous inorganic and organic materials have been used as renewable and safer way for ethylene removal even at very low concentrations. Inorganic solids viz., zeolites [14], zirconia [15], clays [16], silicas [17], alumina [18] and organic materials viz., resins [19,20], polymers [21] and activated carbons [22] have been extensively used as support for the above-mentioned metal ions.…”
Section: Introductionmentioning
confidence: 99%